Protective effect of breastfeeding against childhood leukemia in Zhejiang Province, P. R. China: a retrospective case-control study. Issue 1 (1st January 2019) - Gao, Zhen; Wang, Rui; Qin, Zhao-Xia; Dong, Ao; Liu, Chong-Bin
ABSTRACT: Objectives : Our research investigated the relationship between childhood leukemia and breastfeeding in the P. R. of China. Methods : We conducted a retrospective case-control study from March 2008 to April 2017 at the Children's Hospital of Zhejiang University, Zhejiang province, P. R. of China, which reviewed 958 children who had been diagnosed with leukemia in case group and 785 healthy children in control group. Data were obtained from medical records, and if the medical records were incomplete, we called mothers of children by phone to complete the data. Results : Breastfeeding reduces the risk of childhood leukemia; the effect is greater, if feeding continued for 7–9 months ( p = 0.002). In addition, we suggest that some factors such as maternal age, smoking during pregnancy, abortion history, genetic factors, parents use of hair dye, and the history of using birth control pills before pregnancy can increase the risk of childhood leukemia. Conclusions : This study indicates that promoting breastfeeding for 7–9 months may help lower the childhood leukemia incidence. Our study firstly demonstrates that breastfeeding has protective effects against childhood leukemia in the P. R. of China. Abbreviations : ALL: Acute lymphocytic leukemia; AML: Acute myeloid leukemia